The impact of nasal aspiration with an automatic device on upper and lower respiratory symptoms in wheezing children: a pilot case-control study - Antonio Pizzulli; Serena Perna; Anja Bennewiz; Holger Roeblitz; Salvatore Tripodi; Jakob Florack; Petra Wagner; Stephanie Hofmaier; Paolo Maria Matricardi (BMC, 2018)
Abstract Background The impact of proper aspiration of nasal secretions during upper respiratory infection on the frequency and severity of symptoms of lower airways has never been investigated. The study was aimed at testing if cleaning the nasal cavities of children with recurrent wheezing using an automatic nasal aspirator improves the upper and lower respiratory symptoms during the cold season. Methods Parents of wheezing children (age 3-72 mo.) answered questionnaires and learned using a nebulizer equipped (cases) or not equipped (controls) with an automatic nasal aspirator (DuoBaby, OMRON, Japan). During a 90-days monitoring period parents filled an electronic diary (BreathMonitor, TPS, Rome, Italy) on their child's symptoms of the upper and lower airways. Results Eighty-nine/91 patients (43 cases, 46 controls) completed the study. Less days with upper (25.0% vs 46.4%, p = 0.004) or lower (21.8% vs 32.8%, p = 0.022) airways symptoms and less days with salbutamol inhalation (12.2% vs 16.9%, p < 0.001) were reported by cases than by controls. The episodes of upper respiratory symptoms were shorter [4.3 days (95%CI:3.8-4.9) vs 5.7 days (95%CI:5.0-6.4), p = 0.007] but not less frequent [2.3 (95%CI: 1.8-2.8) vs 2.6 (95%CI:2.2-3.0), p = 0.122] among cases than among controls. Similarly, the episodes of lower respiratory symptoms tended to be shorter [3.8 days, (95%CI: 3.4-4.2) vs 4.4 days, (95%CI: 4.4-6.0), p = 0.067] but not less frequent [1.9 (95%CI:1.5-2.3) vs 2.1 (95%CI:1.7-2.4), p = 0.240] among the group using the nasal aspirator. Conclusions In our pilot study, the use of an automatic nasal aspirator in children with a history of recurrent wheezing was associated with an improved respiratory health during the cold season.